Assessing householder social-ecological resilience in transboundary conditions: The case of the MAP region in southwestern Amazonia - Daniel Callo-Concha; Elisabeth Lagneaux; Rodrigo Zenteno; Oliver Frör (University of Bonn, Center for Development Research (ZEF), 2022)
Land use change is continuously accelerating in the Amazon basin, intensified by road network expansion, farming, ranching, and mining activities, all major drivers of change. This pattern is expected to spread across the continent, fuelled by the economic benefits that road building provides. However, the extent of regional trade-offs regarding ecological stability and the provision of ecosystem services is generally unaccounted for, despite narratives on the loss of resilience and even the imminent trespassing of tipping points becoming common. In the PRODIGY project, we evaluate the social-ecological resilience of rural smallholders in the transboundary MAP (Madre de Dios - Acre - Pando) region in the southwestern Amazon, where the construction of the first transcontinental highway culminated a decade ago. This paper sets a baseline for this endeavour, by distinctively profiling the three country-sites constituting our sample; elucidating the complex system and disturbance and change approaches on which we rely to tackle the challenge; and detailing the implementation of our work. Our preliminary findings confirmed the intrinsic differences among the three country-sites, but also pinpointed crucial ones, like the triggering role of political polarization in Brazil, the mono-dependence on Brazil nut in Bolivia, and the uncertain effects of economic diversification in Peru.
Keywords: 330; Rural livelihoods; human-environmental systems; trans-border situation; complexity; participatory systems analysis; disruption and change; tipping point